Optimization of overhead enclosure monitoring software in a rodent model of osteoarthritis - Helbling, Joel E., author; Santangelo, Kelly, advisor; Easley, Jeremiah, committee member; Kendall, Lonnie, committee member (Colorado State University. Libraries, 2022)
Osteoarthritis (OA) is a degenerative joint disease characterized by pain, inflammation, and decreased range of motion, leading to impaired activities of daily living and reduced quality of life. OA affects between 250 and 500 million people worldwide, contributing to a substantial and sustained economic burden. Given the global pervasiveness of this poorly understood disease process, in vivo OA research relies on both naturally occurring and induced animal models for its study. The Dunkin Hartley guinea pig spontaneously develops degenerative joint disease as early as 3 months of age and represents a well-characterized animal model of primary OA with pathological progression similar to humans. In contrast, secondary OA is caused by non-idiopathic factors, including trauma, and animal models of secondary OA rely on chemical, surgical and non-surgical induction of instability. Open-field testing (OFT) is a behavioral tool which provides objective measurements of mobility outcomes for animals enrolled in musculoskeletal studies and can be paired with overhead monitoring software to non-invasively track voluntary animal movement through the designated arena. However, established protocols for OFT have not been published in the guinea pig. The overarching goal of this project was to optimize OFT in the guinea pig to reduce environmental variability in behavioral testing conditions. The results of this project provided a framework to ensure accurate and reproducible data collection in subsequent studies involving therapeutic interventions to both spontaneous OA and traumatic OA. A hallmark symptom of OA is pain and, as such, the second portion of this work was dedicated to researching cannabidiol (CBD) as an alternative interventional therapeutic to analgesia. Specifically, mobility outcomes assessments were performed during a pharmacokinetic safety study as well as a chronic oral CBD dosing study. Significant differences were analyzed both on baseline (pre-treatment) and on treatment intervention in each phase of this two-part study pertaining to OFT. The results of these studies identified time-of-day effects exist when testing guinea pigs in the open-field and provided preliminary evidence that no adverse short-term behavioral effects exist after oral administration of CBD. The final goal of this project was to design of bioreactor to establish a non-surgical animal model of post-traumatic osteoarthritis (PTOA) in the guinea pig through precision rupture of the anterior cruciate ligament (ACL) by tibial compression and displacement. While this model has been characterized in other rodents, it has not been described in guinea pigs. Work from this portion of the project helped produce a functional bioreactor which will be used initially on cadavers and will ultimately promote in vivo research of interventional treatments for PTOA by establishing reproducible ligament lesions with subsequent degenerative joint pathology.